2020
DOI: 10.3390/jcm9010268
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cartilage Oligomeric Matrix Protein in Late-Stage Osteoarthritis: Association with Clinical Features, Renal Function, and Cardiovascular Biomarkers

Abstract: This study aimed to assess associations between serum cartilage oligomeric matrix protein (sCOMP) and phenotypic characteristics in late-stage hip and knee Osteoarthritis (OA) as well as its correlation with further serum markers of possible comorbidities in the Ulm Osteoarthritis Study. Moreover, the prognostic relevance of preoperative sCOMP concentrations for short-term functionality and pain outcomes after hip or knee joint replacement was explored. Preoperative serum samples and detailed information about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…For example, a recent study showed that among 754 patients with OA undergoing TJR, those with increased serum COMP levels had a larger decrease of the WOMAC stiffness index compared with those with lower values. 151 In terms of safety issues, a recent exploratory retrospective analysis of the anti-NGF tanezumab trials showed that a combination of some biomarkers may be useful to identify patients with knee OA who are at a high risk of rapidly destructive OA and/or TJR. 137 Monitor treatment efficacy Among the various potential roles of biomarkers in OA, their ability to monitor drug efficacy is probably one of the most important, in association with clinical and imaging parameters.…”
Section: Prediction Of Treatment Responsementioning
confidence: 99%
“…For example, a recent study showed that among 754 patients with OA undergoing TJR, those with increased serum COMP levels had a larger decrease of the WOMAC stiffness index compared with those with lower values. 151 In terms of safety issues, a recent exploratory retrospective analysis of the anti-NGF tanezumab trials showed that a combination of some biomarkers may be useful to identify patients with knee OA who are at a high risk of rapidly destructive OA and/or TJR. 137 Monitor treatment efficacy Among the various potential roles of biomarkers in OA, their ability to monitor drug efficacy is probably one of the most important, in association with clinical and imaging parameters.…”
Section: Prediction Of Treatment Responsementioning
confidence: 99%
“…Also, the COMP gene mRNA level in the peripheral blood sample has been reported to be upregulated along with the COMP protein level, in the OA patients, playing a role in the structural integrity of the cartilage through interaction with extracellular matrix proteins by the cell surface integrin receptor [41]. Another study confirmed that the expression of COMP is reduced in the serum of late-stage OA due to proteolytic activity in the affected cartilage as shown in Table 2 [42]. In another study, COMP protein in OASF was downregulated in early-stage OA compared to end-stage OA and showed a positive linear correlation with age, but not significantly correlated with gender.…”
Section: Noncollagenous Biomarkersmentioning
confidence: 84%
“…98,99 In such a design, the CTX-II/COMP combination may be a marker for early diagnosis, evolution, and disease severity. In the study of Riegger et al, 100 conducted on 754 subjects who underwent total joint replacement, serum COMP levels positively correlated with markers of renal (cystatin C, creatinine, estimated glomerular filtration rate-eGFR) and cardiac (N-terminal propeptide of brain natriuretic peptide) function. After adjustment for eGFR, COMP levels were still associated with WOMAC scale and sub-scales, 6 months after surgery.…”
Section: Collagen Type II Degradation Products and Comp As Biomarkersmentioning
confidence: 98%